Evaluation of self-reported confidence amongst radiology staff in initiating basic life support across hospitals in the Cape Town Metropole West region - Vorster, Isak Dawid (Division of Radiology, 2019)
Introduction: The immediate response to a cardiac arrest is regarded as one of the most time-critical interventions in clinical medicine. First responders for cardiac arrest in imaging departments are often radiology staff. The study aim was to determine radiology staff-members' confidence in initiating basic life support. Methods: A multi-centre, cross-sectional survey was conducted using peer-validated, anonymous questionnaires. Confidences were recorded using a 10-point Likert scale for recognising cardiac arrest, securing an airway, providing rescue breaths and initiating cardiac compressions. Questionnaires were distributed to and completed by radiology staff working in public sector hospitals within the Cape Town Metropole West. Due to the limited subject pool a convenience sample was collected (with no power calculation). Data were therefore statistically analysed using only summary statistics (mean, standard deviation (SD), proportions, etc.). Detailed between group comparisons were not made, given the sample size and type. Results: We disseminated 200 questionnaires, of which 74 were completed (37%). There were no incomplete questionnaires or exclusions from the final sample. Using the Likert scale, the mean ability to recognise cardiac arrest was 6.45 (SD±2.7), securing an airway 4.86 (SD±2.9), and providing rescue breaths and initiating cardiac compressions 6.14 (SD±2.9). Only 2 (2.7%) of the participants had completed a basic life support course in the past year, while 11 (14.8%) had never completed any basic life support course and 28 (37.8%) had never completed any type of life support or critical care course. Radiologists, radiology trainees and nurses had the greatest confidence in providing rescue breaths and initiating cardiac compressions from all the groups. Conclusion: The study demonstrates substantial lack of confidence in providing basic life support in a large part of the staff in Cape Town’s public hospital imaging departments. The participants indicated that regular training and improved support systems would increase confidence levels and improve skills.